2014
DOI: 10.15252/embj.201488784
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Notch signaling requirements in the specification of hematopoietic stem cells

Abstract: Hematopoietic stem cells (HSCs) require multiple molecular inputs for proper specification, including activity of the Notch signaling pathway. A requirement for the Notch1 and dispensability of the Notch2 receptor has been demonstrated in mice, but the role of the remaining Notch receptors has not been investigated. Here, we demonstrate that three of the four Notch receptors are independently required for the specification of HSCs in the zebrafish. The orthologues of the murine Notch1 receptor, Notch1a and Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 62 publications
5
95
0
Order By: Relevance
“…It was also previously reported that a decrease in OPN‐positive cells in the endosteal niche of diabetic mice correlates with decreased expression levels of N‐cadherin and β‐catenin on LT‐HSCs (Chiba et al , 2013). Upon aging, a switch in Wnt‐signaling in aged HSCs occurs (Roozen et al , 2012; Florian et al , 2013; Kim et al , 2014) which thus raises the possibility that the reduction in stromal OPN upon aging might likely contribute to or at least further enhance aging‐related Wnt pathway dysregulation. Analysis of the cytokine/chemokine composition of the BM extracellular fluid upon aging confirmed a previously published increase in the pro‐inflammatory protein RANTES in BM upon aging (Fig EV1E).…”
Section: Discussionmentioning
confidence: 99%
“…It was also previously reported that a decrease in OPN‐positive cells in the endosteal niche of diabetic mice correlates with decreased expression levels of N‐cadherin and β‐catenin on LT‐HSCs (Chiba et al , 2013). Upon aging, a switch in Wnt‐signaling in aged HSCs occurs (Roozen et al , 2012; Florian et al , 2013; Kim et al , 2014) which thus raises the possibility that the reduction in stromal OPN upon aging might likely contribute to or at least further enhance aging‐related Wnt pathway dysregulation. Analysis of the cytokine/chemokine composition of the BM extracellular fluid upon aging confirmed a previously published increase in the pro‐inflammatory protein RANTES in BM upon aging (Fig EV1E).…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling regulates HSC formation through both direct and indirect mechanisms (Clements et al, 2011;Hadland et al, 2004;Kim et al, 2014;Kobayashi et al, 2014). Our data demonstrate that Notch signaling is required for the expression of gata2b in hemogenic endothelium.…”
Section: Regulation Of Gata2b Expressionmentioning
confidence: 65%
“…Both cell-autonomous and non-cell-autonomous Notch signaling is required for the formation of vertebrate HSCs (Hadland et al, 2004;Kim et al, 2014). Notch signaling is required for both arterial specification and HSC formation from arterial vasculature.…”
Section: Gata2b Is Regulated By Notch Signalingmentioning
confidence: 99%
See 2 more Smart Citations